P‐203: Late‐News Poster: Novel Techniques for Highly Stable Luminescent Perovskite Halide Quantum Dots. Issue 1 (30th May 2018) - Sinatra, Lutfan; Lutfullin, Marat; Abbas, Abdullah Saud; Pan, Jun; Bakr, Osman M.
Abstract : Perovskite quantum dots (QDs) are promising materials for display application due to their high optical properties, such as: high PLQY, narrow FWHM and tunable emission wavelengths. The present work shows the further progress in enhancement of perovskite QDs stability, resistance to photodegradation and PL quenching at high temperatures.